2021
DOI: 10.1186/s12890-020-01384-4
|View full text |Cite
|
Sign up to set email alerts
|

Severe pneumonia in adults caused by Tropheryma whipplei and Candida sp. infection: a 2019 case series

Abstract: Background Whipple’s disease is a chronic infectious disease caused by the Gram-positive bacterium Tropheryma whipplei (TW), which not only affects the gastrointestinal tract and causes malabsorption of nutrients, but several other systems, such as the cardiovascular system, central nervous system, the joints, and the vascular system, can also be simultaneously involved. The aim of this report was to be able to alert the clinician to severe pneumonia caused by TW combined with Candida sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Our study also confirm that T. whipplei is an etiologic pathogen in acute respiratory infections (Lagier et al, 2017). T. whipplei could be co-infected with Pneumocystis jirovecii and Candida albicans, as reported in previous cases (Li et al, 2021;Yan et al, 2021), or leaded to pulmonary infection alone (Guo e t a l . , 2 0 2 1 ) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study also confirm that T. whipplei is an etiologic pathogen in acute respiratory infections (Lagier et al, 2017). T. whipplei could be co-infected with Pneumocystis jirovecii and Candida albicans, as reported in previous cases (Li et al, 2021;Yan et al, 2021), or leaded to pulmonary infection alone (Guo e t a l . , 2 0 2 1 ) .…”
Section: Discussionsupporting
confidence: 89%
“…Our study also confirm that T. whipplei is an etiologic pathogen in acute respiratory infections ( Lagier et al., 2017 ). T. whipplei could be co-infected with Pneumocystis jirovecii and Candida albicans , as reported in previous cases ( Li et al., 2021 ; Yan et al., 2021 ), or leaded to pulmonary infection alone ( Guo et al., 2021 ). Moreover, we also found that immunocompromised patients were more likely to be diagnosed with pneumonia, suggesting that T. whipplei should be considered more as a pathogen when detected in BALF in immunocompromised patients with clinical symptoms.…”
Section: Discussionsupporting
confidence: 61%
“…Our case is the first diagnosed case of pulmonary cavity caused by Tropheryma whipplei . In addition to our case, we identified 19 patients with lung parenchymal involvement in the literature [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Their clinical, radiologic, and pathological features were provided in the Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] In addition to monomicrobial infection, TW has been found to cause severe pneumonia due to co-infection with opportunistic species. [ 46 ] Chronic pulmonary disease has distinctive clinical manifestations. In these cases, lung involvement appears as an interstitial or granulomatous lung disease that may mimic pulmonary sarcoidosis or fungal infections.…”
Section: Discussionmentioning
confidence: 99%